Assessment of the Efficacy of Novel Surgical Techniques in the Treatment of Chronic Sinusitis - Bharti, Saloni; Aarya, Adity (Journal of Neonatal Surgery, 2025)
Background: Chronic sinusitis' prevalence and debilitating nature affect patients' quality of life. Functional endoscopic sinus surgery (FESS) and other conventional surgeries are effective, but patients may experience intermittent symptom relief and long recovery times. Smaller surgeries like image-guided endoscopic sinus surgery and balloon sinuplasty may improve patient outcomes. This study compares these novel techniques to sinus surgery in recovery time, symptom improvement, patient satisfaction, and recurrence rates. Methods: This prospective cohort study included 40 chronic sinusitis patients who did not respond to treatment. Twenty patients underwent conventional sinus surgery, while twenty underwent innovative procedures. The main outcomes were surgery recovery time, VAS symptom improvement, and SNOT-22 score reduction. Secondary outcomes included six-month symptom recurrence, patient satisfaction, and complications. Statistics were used to compare treatment efficacy using t-tests and chi-square tests. Results: Innovative surgical procedures resulted in a significantly faster recovery time (12.4 ± 3.2 days) compared to traditional surgery (21.6 ± 4.5 days) (p < 0.001). The group that underwent novel surgery showed greater symptom relief, with a decrease in SNOT-22 scores (27.8 ± 5.3 vs. 21.2 ± 6.1, p = 0.004) and a significant increase in VAS improvement scores (7.4 ± 1.2 vs. 5.8 ± 1.1, p = 0.002). The novel group had significantly higher patient satisfaction (8.2 ± 1.4 vs. 6.1 ± 1.3) with a p-value < 0.001. Despite the novel group's lower complication rate (5% vs. 15%), the two groups were not statistically different. Recurrence at six months was lower in the novel group (10% vs. 25%), but not statistically significant (p = 0.18). Conclusion: New sinus surgery methods deliver faster recovery, better symptom relief, and higher patient satisfaction. The novel group had lower recurrence rates, but longer-term studies are needed to confirm these results. These results suggest chronic sinusitis treatment with minimally invasive surgery